Impact of Gestational Exposure to 2,3,7,8-Tetrachlorodibenzo-P-Dioxin on T Lymphocyte Development - (:unkn) unknown (My University, 2014)
2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a ubiquitous environmental contaminant and the best characterized agonist of the arylhydrocarbon receptor (AHR), a transcription factor crucial to the detoxification of numerous xenobiotics. Studies in animals show that TCDD is immunosuppressive in adult exposures, and epidemiological studies have found an association between TCDD exposure and hematologic cancers. Additionally, developmental exposure to TCDD has been shown to increase the likelihood of autoimmunity and to impair immune response to later-life infections. The cells of the immune system are all descended from multipotent hematopoietic stem cells (HSCs) that originate in the fetus. This multipotency, defined as the ability to develop into several different cell types, suggests that any impact on HSCs potentially affects all cells arising from the original HSCs throughout the life course. During particularly sensitive timepoints such as puberty and pregnancy, alterations initiated by early life exposures can be triggered to cause immune disorder by shifts in hormone levels, stress, or other endogenous means. The effect that developmental exposures have on later life immune disease is not completely understood, but epidemiological statistics suggest that the rise in immunological disease is associated with a changing environment, whether due to chemical, microbial, or as-yet-unknown contributing factors. We investigated the effects of developmental AHR activation on later-life immune outcomes and used a mouse model to examine T lymphocyte development following gestational exposure to environmentally relevant levels of TCDD. We found that developmental exposure to TCDD significantly decreased the lymphocyte differentiation potential of HSCs, and that this effect occurs through the fetal AHR. We also found that AHR signaling is involved in crosstalk with the Notch1 gene--a gene which has been linked to over half of the cases of T cell acute lymphoblastic leukemia. These studies support the role of developmental exposure to environmental contaminants in the development of immune disease and may lead to multiple public health focused interventions such as development of treatments, implementation of preventative measures, and changes in environmental policy.
Keywords: AHR; Developmental Immunotoxicology; Notch; TCDD